Examining Perceived Coercion in Drug Treatment Courts - Bruzios, Kathryn E. (International journal of offender therapy and comparative criminology, 2023)
While perceptions of voluntary consent have been studied among participants in Mental Health Courts (MHC), little is known about coercion among participants in Drug Treatment Courts (DTC), the most common type of specialty court. The purpose of the present study was to examine perceptions of coercion at enrollment among participants (N = 85) in two Massachusetts DTCs. Results indicated that, on average, participants reported low levels of perceived coercion (M = 1.67, SD = 1.23), which suggests that most individuals did not perceive their decision to enroll in DTC to be coercive. However, further research is needed to delineate whether clinical or procedural variations exist within DTCs, if levels of perceived coercion predict DTC participant outcomes, and if subpopulations experience higher or lower levels of coercion.